An Analysis On The Value Of Justness In The Help By Kathryn Stocket - Vivin Afini (Metonimia: Jurnal Sastra dan Pendidikan Kesusastraan, 2023)
Objectives of this study are to explain the value of justness in the protagonist of the story in the novel of The Help and to find out the view of justness reflected in the protagonist of the story in the novel The Help. In this study, the writer used descriptive method and two kinds of approaches. They are objective approach and psychological approach. The main characters shows bravery, responsibility, sacrifice, and struggle. Moreover, at least there are seven related values leading to justness of this Kathryn Stockett’s The Help. Those are bravery, kindness, equality, love, rights to be free, change, and sympathy. Hopefully this study could help students of literature sharpening their sense of care and improving their conduct of living in the middle of their society and enrich their knowledge of literary work. Moreover, the result of this study may provide some useful lessons to face life. to respect other people, without care about someone’s religion, race, and culture